DIVERSIFIKASI PRODUK DAN OPTIMASI MANAJEMAN USAHA PADA UMKM RESELLER GETA.STORE - Made Agus Putra Subali; I Gusti Rai Agung Sugiartha; I Putu Aditya Putra; I Made Andre Sentanu (Sewagati, 2023)
The partner product marketing process is carried out on the Shopee e-commerce platform under the name Geta.Store. statistically, the assessment obtained by Geta.Store from the Shopee platform is very good. The high number of transactions makes the partner business management process very complex and takes a long time to process, especially in the process of financial transactions which include (1) purchasing products from suppliers, (2) selling products to buyers, and (3) the process of recording payments. Currently all of these processes are done manually by writing them in the transaction journal. To further optimize the partner business management process, the team provides assistance in the form of a web application, in which the application contains the three features needed. In addition, the team diversified one of the plain t-shirt products by adding exclusive designs. Based on the activities that have been carried out, the results of the system assistance provided are able to overcome partner problems and improve product quality by diversifying partner plain t-shirt products.